Protective effects of peel and seed extracts of Citrus aurantium on glutamate-induced cytotoxicity in PC12 cell line - Hosseini, Azar; Sadeghnia, Hamid Reza; Rajabian, Arezoo (Folia Neuropathologica, 2016)
Oxidative stress and apoptosis contribute to neuronal degeneration in many neurodegenerative diseases such as Alzheimer’s disease. Glutamate is a major excitatory neurotransmitter in the central nervous system (CNS) and is considered responsible for the pathogenesis of many neurological disorders. Reactive oxygen species (ROS) production is thought to be involved in glutamate-induced apoptosis process. In this study, the neuroprotective effects of Citrus aurantium in the glutamate-induced rat’s adrenal pheochromocytoma cell line (PC12 cells) were investigated. The cell viability and apoptotic cell death were measured using MTT and propidium iodine (PI)-staining methods, respectively. In addition, intracellular ROS and malondialdehyde (MDA) levels were determined by fluorometric methods. The results showed that glutamate cytotoxicity in PC12 cells was accompanied by an increment of MDA content, ROS generation, and apoptotic induction. However, pretreatment with peel and seed extracts of C. aurantium significantly reduced MDA content, ROS generation, and apoptotic cells. All these ﬁndings indicated that C. aurantium protected PC12 cells against glutamate-induced apoptosis by inhibiting ROS production. Therefore, the present study supports that C. aurantium extracts possess neuroprotective effects against glutamate-induced toxicity in PC12 cell line. The protective effect of C. aurantium might be attributed to its antioxidant properties.